Conventional wastewater treatment methods for the removal of EPs - Wan Norfazilah, Wan Ismail; Nurul `Azyyati, Sabri; Nurlin, Abu Samah; Siti Umairah, Mokhtar (Springer Nature, 2023)
Pharmaceuticals, personal care and beauty products, pesticides, nanoparticles and nanomaterials, surface-active agents, industrial substances and additives, and pathogens are the prominent classes of emerging pollutants (EPs). One of the current major growing environmental problems is the noticeable amount of these EPs that are present in domestic, municipal, and industrial wastewaters treated by conventional wastewater treatment methods. They are released continuously into the environment due to increasing demand for chemical-based products. However, a majority of the EPs are not controlled or monitored by national or international legislation. Even worse, they can cause direct or indirect harm to human beings and the surrounding ecosystem even at low concentrations. This chapter reviews the concept and applications of conventional wastewater treatment methods to remove EPs in order to understand their limitations. A particular focus is given to filtration, sedimentation, coagulation/flocculation, and activated sludge. Although these conventional methods are intended for removing particles in suspension and colloidal form, organic substances in dissolved state, essential nutrients, and pathogens from wastewater, EPs eventually could also be removed depending on their persistence, physical and chemical properties, treatment methods used, and operational and environmental conditions involved. The most significant groups of EPs that could potentially be removed by the conventional methods are also described. Since these conventional methods cannot guarantee the complete removal of various EPs, it is necessary to study suitable long-term and effective alternatives in the treatment technologies.